2021
DOI: 10.1063/5.0059750
|View full text |Cite
|
Sign up to set email alerts
|

Traveling of extreme events in network of counter-rotating nonlinear oscillators

Abstract: We study the propagation of rare or extreme events in a network of coupled nonlinear oscillators, where counter-rotating oscillators play the role of the malfunctioning agents. The extreme events originate from the coupled counter-oscillating pair of oscillators through a mechanism of saddle-node bifurcation. A detailed study of the propagation and the destruction of the extreme events and how these events depend on the strength of the coupling is presented. Extreme events travel only when nearby oscillators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…A detailed study of the synchronization of time-varying networks was also found in [15]. Te literature on synchronization is huge, and one may refer to [1,3,4,6,8,10,[16][17][18][19][20][21][22] and references therein. Recently, several studies have dealt with the synchronization of complex networks with higher-order interactions [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 97%
“…A detailed study of the synchronization of time-varying networks was also found in [15]. Te literature on synchronization is huge, and one may refer to [1,3,4,6,8,10,[16][17][18][19][20][21][22] and references therein. Recently, several studies have dealt with the synchronization of complex networks with higher-order interactions [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 97%
“…In the study of temporal dynamics of many dynamical systems, the occurrence of infrequent but recurrent comparatively high or low amplitude events might have qualitative similarities with occasional large events being recorded in many real-world phenomena. The emergence of EEs is reported in several dynamical systems such as FitzHugh-Nagumo oscillators, 29,[31][32][33][34][35] Hindmarsh-Rose model, 36 Liénard system, 37 Ikeda map, 25 Josephson junctions, 38 Ginzburg-Landau model, 39 nonlinear Schrödinger equation, 40 micromechanical system, 41 climatic models, 42 ecological model, 43 mechanical system, 44 and electronic circuits, 45 to name but a few. In addition, we also find some experimental evidence of the appearance of EEs, such as in laser systems, 46 epileptic EEG studies in rodents, 47 annular wave flume, 48 and laser systems, 49 to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Lebedev et al demonstrated that rotations in neural population activity could represent spatiotemporal neural patterns best described as travelling waves [61]. Travelling waves are frequently encountered in neural datasets [62][63][64][65][66], including motor learning data [67], and reach-to-grasp movements [51,68], as well as datasets for RNNs trained for muscle activity production [69] and decision-making [41]. Additionally, Proix et al [70] demonstrated that a temporal covariance matrix structure creates a horseshoe artefact -a frequently encountered consequence of dimensionality reduction methods that yields rotations of state-space trajectories.…”
mentioning
confidence: 99%